Environmental economics : concepts, methods, and policies - Thampapillai, Dodo J. (South Melbourne ; New York : Oxford University Press, 2002)
This book provides comprehensive treatment of environmental economics. This work illustrates a novel approach to the formulation of environmental policy by developing the pertinent concepts and methods of economics by establishing links between the environment and the economy by recourse to the laws of thermodynamics.
Part I. The Environment and the Economy 1. The Environment and Economics 2. The Economic System Revised Part II. Microeconomics and the Environment 3. The Market Model and it's Failure 4. Public Goods and Externalties 5. Consumer Demand and the Environment 6. Production, Costs, Supply and the Environment 7. Valuation of Environmental Goods and Services 8. Policy Frameworks i Resource Management 9. Policy Frameworks ii Regualtion and Instruments Part III. Macroeconomics and the Environment 10. Some Important Concepts in Macroeconomics 11. Environmental Capital: Investment and Depreciation 12. The Environment and Income Determination 13. The Environment in Other Macroeconomic Models Part IV. Revisiting the Scarcity Debate 14. Revisiting the Scarcity Debate. Notes Includes index.
Includes bibliographical references (p. 202-210) and index.
Keywords: Economic development -- Environmental aspects; Environmental policy -- Economic aspects